VISUAL ARTS OF SUKATANI BAND ON SOCIAL MEDIA AS PARTICIPATORY MOVEMENT AFFECTS THE GOVERNMENT POLICIES - Sari Wulandari; Elmi Novita (Srawung: Journal of Social Sciences and Humanities, 2025)
This research examines the Sukatani Band case and their controversial song "Bayar Bayar Bayar," which criticized extortion practices by certain Indonesian police officers and became a voice against social injustice. Through a qualitative case study approach, this research investigates how social movement activity stimulates the emergence and proliferation of visual arts on social media as mechanisms of reflexive response and policy influence. The study analyzes the rise of public expression on Instagram triggered by pressure and alleged intimidation experienced by Sukatani from police institutions, including coercion to reveal their identity and its social impact. Findings reveal that institutional repression paradoxically intensified counter-hegemonic artistic production, with Sukatani's forced apology generating 255 posters from 140 artists within five days. Hashtags #KamiBersamaSukatani and #IndonesiaGelap generated over 600,000 social media posts, ultimately compelling police to reverse their prohibition stance. The study demonstrates how social media has become a strategic space for spreading critical messages, building solidarity, and pushing for policy change. Analysis highlights the role of artists as organic intellectuals who strengthen resistance against political hegemony through artwork and visual communication. The research operationalizes Gramscian hegemony theory for digital environments, revealing how apparatuses of power and apparatuses of hegemony operate simultaneously in social media spaces. Although freedom of expression remains hampered by state repression, public participation through visual arts proves an effective tool in contemporary democracy to voice inequality and dismantle oppressive structures.